The Effect of Text Structure Instruction on Improving Tenth Grade Female Students’ Expository Writing - Khataibeh, Almaza Khataibeh; Magableh, Naser (Jordan Journal of Educational Sciences, 2016)
This study aimed at investigating the effect of text structure instruction on tenth grade female students’ expository writing in Jordan. The researchers prepared a list that included sections of expository writing; which are (introduction, body, conclusion, and writing style). and a set of skills (function indicators). The researchers also constructed a test to measure the performance of the students in expository writing sections. The test consisted of a set of questions. Each question contains a statement or paragraph, that considered as stimulation for students’ thinking and a function indicator refers to expository writing. The researchers also developed a standard for evaluating the performance of the test. The subjects of the study consisted of (91) female Students, who were divided into two classes, for the academic year (2014/2015) and the two groups purposefully selected. The Experimental group (46) was studies the reading texts in a text structure manner and the control group (45) studies the texts by conventional method. The results showed a statistically significant differences between the means of the performance of study subjects in each section of the four expository writing sections, in the favor of experimental group